Subsídios a reformulação da norma brasileira NB-140/65 - tipificação de edifícios em porto alegre - Hirota, Ercília Hitomi (Semina: Ciências Exatas e Tecnológicas, 2004)
This paper takes of the dissertation presented to the Civil Engineering Post Graduation Course of UFRGS and its objective is to provide systematíc standardization of typical building profects, specially in respect to the reformulation of the brasilian Code NBâ€”140, considered here as the fundamental background. It consists of an exploratory study of those variables, which define the physical structure of buildings through statistical analysis of data colected in Porto Alegre, The data of this work suggested the necessity of developing the researches on this subject provide Information needed in this area.